Pengaruh Pola Makan terhadap kadar hemoglobin Pada Anak Pra Sekolah - Rosalinna Rosalinna; Sugita Sugita (Poltekkes Kemenkes Surakarta, 2020)
Background: Pre school children need adequate nutrition for growth and development, as one of the most vulnerable groups is primarily anemia. Nutritional disorders of anemia can be caused by various factors, one of which is a diet (amount, frequency and variety ) that does not meet the balance. Objective to analyze The Effect of Diet on Hemoglobin Levels In Pre-School children. Methods: Cross-sectional study was conducted on 28 chlidren. Sampling is done by Purposive Sampling technique. Data collect from food Record and misson Hb. Data analyze used Pearson product moment correlation test and Multiple Regression Analysis. Results: The results of this study obtained the average hemoglobin level of children is 10.18 (0.99). The results of the test on energy intake (ρ = 0.820), iron intake (ρ = 0.300), vitamin C intake (ρ = 0.300) which states no significant relationship with hemoglobin levels. Protein intake (ρ = 0,007), variation (ρ = 0,000), and frequency (ρ = -0,035) have significant relationship with hemoglobin level. Multivariate analysis of dietary variations significantly influenced hemoglobin levels in pre-school children (ρ = 0.000, r = 0.0636; R2 = 0.405). Conclusions: That daily intake, iron intake and vitamin C alone have no effect on hemoglobin, but it is necessary to increase protein intake, eating frequency setting especially variation in food menu. Required intervention strategies to increase intake, selection of foodstuffs, processing, presentation to children for iron absorption and control of anemia can be solved.